2020
DOI: 10.1242/jcs.239384
|View full text |Cite
|
Sign up to set email alerts
|

F-actin flashes on phagosomes mechanically deform contents for efficient digestion in macrophages

Abstract: The mechanism and role of transient F-actin recruitment or F-actin “flashes” on phagosomes remains enigmatic. Here we provide a comprehensive characterization of F-actin flashing dynamics on phagosomes including receptor and signaling involvement. F-actin flashes predominate during the integrin-driven CR-mediated phagocytosis. F-actin flashes begin shortly after internalization and persist on phagosomes for ∼3 minutes before disassembling and reassembling several times within the first hour. Strikingly, the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…4A), similar to the macrophage actin flash described previously (22,26). The frequency of the actin flash is reported to be around 3 to 4 min from the moment of F-actin assembly to F-actin disassembly and is more prevalent within the first hour after phagocytosis (22,23). To determine whether the persistent R265 phagosomal F-actin "flashed," we performed live-cell microscopy.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…4A), similar to the macrophage actin flash described previously (22,26). The frequency of the actin flash is reported to be around 3 to 4 min from the moment of F-actin assembly to F-actin disassembly and is more prevalent within the first hour after phagocytosis (22,23). To determine whether the persistent R265 phagosomal F-actin "flashed," we performed live-cell microscopy.…”
Section: Resultssupporting
confidence: 62%
“…This is likely due to the rapid phagolysosome formation that followed F-actin cage disruption. Through a process that is not well understood, phagolysosome formation appears to have an inverse relationship with phagosomal F-actin (22,23). We speculate that phagolysosome formation overrides the signaling pathways that are responsible for maintaining the persistent F-actin cage of hypervirulent C. gattii.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Most studies reporting the inhibitory role of actin limited their investigation to early-stage phagosomes. In particular, transient accumulations of actin were observed to surround a subpopulation of purified immature phagosomes which prevented association with endolysosomal vesicles ( 125 , 137 ). It was also demonstrated that de novo actin assembly on nascent phagosomes increases under cell stress conditions when the phagocytic or endocytic pathway is overloaded with digestive cargo ( 125 ).…”
Section: Other Factors Involved In Pl Fusionmentioning
confidence: 99%
“…It has been postulated that transient actin assembly on endolysosomal and phagosomal systems slows phagosome-lysosome fusion when these vesicles contain more cargo than they have the capacity to digest ( 125 ). Actomyosin association is a possible complimentary mechanism that can either delay phagosome migration to the perinuclear region to allow them extra time to preprocess internalized phagosomal content, and to not outpace the availability of lysosomes for fusion ( 131 , 137 ).…”
Section: Other Factors Involved In Pl Fusionmentioning
confidence: 99%